Performance and Egg Quality of Laying Ducks Fed Diets Containing Cassava (Manihot esculenta Crantz) Leaf Meal and Golden Snail (Pomacea canaliculata) - Sumiati Sumiati; A. Darmawan; W. Hermana (Tropical Animal Science Journal, 2020)
The objective of this study was to evaluate the effect of feeding cassava leaf meal and golden snail on performances, chemical, and physical qualities of local duck egg. The experiment used 180 Pajajaran laying ducks of 20 weeks of age and was offered dietary treatments up to 26 weeks of age. The experiment was conducted in a completely randomized design with a 3 x 2 factorial arrangement. The first factor was the treatment of cassava leaf meal consisted of 3 levels, i.e., 0%, 5%, and 10%. The second factor was the treatment of golden snail consisted of 2 levels, i.e., 0% and 10%. Each experimental unit used three replicates and each replicate consisted of ten ducks. The results showed that there was no interaction effect of cassava leaf meal and golden snail treatments on laying duck performances and egg qualities. There were significant effects of cassava leaf meal and golden snail treatments (p<0.05) on egg production, feed intake, egg mass, egg index, and egg yolk color. However, egg weight, feed conversion ratio, yolk fat, yolk cholesterol, and yolk TBARS values, albumen weight, eggshell weight, shell thickness, and Haugh unit values were not affected (p>0.05) by treatments of cassava leave meal and golden snail. The utilization of 10% cassava leaf meal in the diet significantly improved egg production, feed intake, egg mass, and yolk color (p<0.05). The lowest egg index was found in the eggs produced by ducks fed diet containing 5% cassava leaf meal, but it is still within the normal range. Ducks fed a diet containing 5% golden snail significantly had higher feed intake, egg mass, percentage of albumen, and yolk color. It was concluded that there was no interaction effect of cassava leaf meal and golden snail treatments on laying duck performances and egg qualities. A diet containing 10% cassava leaf meal or a diet containing 5% golden snail had the greatest effects on the performance and physical quality of egg without affecting the chemical quality of the egg.